2009
DOI: 10.1016/j.biopsych.2008.12.004
|View full text |Cite
|
Sign up to set email alerts
|

Tumor Necrosis Factor Antagonism Normalizes Rapid Eye Movement Sleep in Alcohol Dependence

Abstract: Background-In alcohol dependence, markers of inflammation are associated with increases in rapid eye movement (REM) sleep, which is thought to be a prognostic indicator of alcohol relapse. This study was undertaken to test whether blockade of biologically active tumor necrosis factor-α (TNF-α) normalizes REM sleep in alcohol-dependent adults.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
45
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 50 publications
(48 citation statements)
references
References 33 publications
3
45
0
Order By: Relevance
“…Species specificities between humans and animals, and also between mice, rats and rabbits have been observed for numerous other immune factors (Mestas and Hughes, 2004). Indeed, several previous studies also found distinct species differences in the impact of cytokine administration and infections on sleep architecture (Irwin et al, 2009;Pollmächer et al, 2000;Raison et al, 2010;Zamarrón et al, 2004).…”
Section: Discussionmentioning
confidence: 85%
See 2 more Smart Citations
“…Species specificities between humans and animals, and also between mice, rats and rabbits have been observed for numerous other immune factors (Mestas and Hughes, 2004). Indeed, several previous studies also found distinct species differences in the impact of cytokine administration and infections on sleep architecture (Irwin et al, 2009;Pollmächer et al, 2000;Raison et al, 2010;Zamarrón et al, 2004).…”
Section: Discussionmentioning
confidence: 85%
“…In pilot studies, patients with rheumatoid arthritis and obstructive sleep apnea showed a decrease in sleepiness after blocking of IL-1 and TNF-signaling, respectively (Omdal and Gunnarsson, 2005;Vgontzas et al, 2004). In another study, abstinent patients with alcohol dependence showed a robust decrease in REM sleep following treatment with the TNF antagonist etanercept (Irwin et al, 2009). Surprisingly, in these human studies TNF blockade did not alter polysomnographic signs of NonREM sleep (Vgontzas et al, 2004;Irwin et al, 2009), which contrasts with findings in rabbits, where i.c.v.…”
Section: Introductionmentioning
confidence: 79%
See 1 more Smart Citation
“…In human opiate addicts, the level of TNF-α expression in the brain (locus coeruleus) is higher than that in control subjects (Dyuizen and Lamash 2009). Levels of circulating TNF-α are altered in alcoholics, opiate addicts, and cocaine or marijuana abusers (Baldwin et al 1997;Peng et al 1999;Irwin et al 2007Irwin et al , 2009Gonzalez-Quintela et al 2008;Sacerdote et al 2008;Li et al 2009;Franchi et al 2010), and TNF-α may be a candidate biomarker of alcohol abuse and alcoholism (Achur et al 2010). In our study in animal, TNF-α (−/−) mice were more sensitive to METH self-administration and had a higher motivation for getting METH than wild-type mice.…”
Section: Discussionmentioning
confidence: 99%
“…Yet reports of the level of circulating TNF-α in human alcoholics, opiate addicts, and cocaine or marijuana abusers are not consistent. Some reports show that the level increases (Gonzalez-Quintela et al 2008;Peng et al 1999;Irwin et al 2009), and others show that the level decreases or does not change (Baldwin et al 1997;Irwin et al 2007;Sacerdote et al 2008;Li et al 2009;Franchi et al 2010). In animals, repeated administration of psychostimulants or opiates induced TNF-α production in the brain or immune system (Friedman and Eisenstein 2004;Nakajima et al 2004;Niwa et al 2007a; Kubera et al 2008).…”
Section: Introductionmentioning
confidence: 99%